Endocrine disorders and fertility and pregnancy: An update - Bendarska-Czerwińska, Anna; Zmarzły, Nikola; Morawiec, Emilia; Panfil, Agata; Bryś, Kamil; Czarniecka, Justyna; Ostenda, Aleksander; Dziobek, Konrad; Sagan, Dorota; Boroń, Dariusz; Michalski, Piotr; Pallazo-Michalska, Veronica; et al. (Frontiers in Endocrinology, 2023)
It is estimated that more and more couples suffer from fertility and pregnancy maintenance disorders. It is associated with impaired androgen secretion, which is influenced by many factors, ranging from genetic to environmental. It is also important to remember that fertility disorders can also result from abnormal anatomy of the reproductive male and female organ (congenital uterine anomalies – septate, unicornuate, bicornuate uterus; acquired defects of the uterus structure – fibroids, polyps, hypertrophy), disturbed hormonal cycle and obstruction of the fallopian tubes resulting from the presence of adhesions due to inflammation, endometriosis, and surgery, abnormal rhythm of menstrual bleeding, the abnormal concentration of hormones. There are many relationships between the endocrine organs, leading to a chain reaction when one of them fails to function properly. Conditions in which the immune system is involved, including infections and autoimmune diseases, also affect fertility. The form of treatment depends on infertility duration and the patient's age. It includes ovulation stimulation with clomiphene citrate or gonadotropins, metformin use, and weight loss interventions. Since so many different factors affect fertility, it is important to correctly diagnose what is causing the problem and to modify the treatment regimen if necessary. This review describes disturbances in the hormone secretion of individual endocrine organs in the context of fertility and the maintenance of pregnancy.